Radial Distributions of Active Species in Plasmas and Afterglows - A. Ricard; J. Margot; S. G. Oh (Plasmas Afterglows with \(N_2\) for Surface Treatments- Edition 2, 2022)
The radial distributions of plasma and afterglow radiative species have been analysed with optical fibers connected to an optical spectrometer. With an optical fiber of dia. giving a detected light resolution of about at a distance, the long time afterglow (LA-10-2 s) was studied in a large volume reactor (5 liters). At pressure of 6-8 Torr, flow rate slpm, the LA- was a jet of dia. with densities of -atoms and metastable molecules of and , respectively. By putting a horizontal slit of in front of the dia. optical fiber, a light beam of dia. was detected across an afterglow tube of dia. In a RF plasma at 8 Torr, , Bessel typed profiles were recorded for all the radiative bands in the pink afterglow and flat profiles of the band in the late afterglow. The band is produced in the late afterglow by -atoms rebounding on the tube wall, explaining its flat profile. In the pink afterglow, the band is mainly produced by collisions of the and is destroyed on the tube wall, which explains its Bessel profile. With a small content into , the and N2(A) states in the pink afterglow are destroyed, lowering the emission that were only produced by the atoms, yielding a flat profile. A radial profile was also obtained with a collimator set on the optical fiber and moved along the radial axis of a surface wave (SW) plasma. With a SW plasma, the electric field (E) reaches a maximum value on the tube wall giving high energy to electrons. As a consequence, the Ar metastable atoms produced by high energy electrons and destroyed by low energy electrons ( unsensitive to E) will show radial profiles of which the shapes were analysed to determine the metastable excitation ) and de-excitation ( ) rates. In Ar SW plasmas at Torr, , it was determined that and as for a DC positive column at same electron density : . 3D spatial distributions of the intensity of the optical thin ArI549.6 nm line was measured in DC and SW plasma columns at 150 mTorr inside tubes of dia. and long. Bessel-type radial distributions were found in the Ar DC column and more rounded profiles in the Ar SW plasmas at 600-900 MHz, with hollow shapes at the plasma end.